Evaluation of the Memory Effect on Gold-Coated Silica Adsorption Tubes Used for the Analysis of Gaseous Mercury by Cold Vapor Atomic Absorption Spectrometry. (25th March 2013) - Rahman, Mohammad Mahmudur; Brown, Richard J. C.; Kim, Ki-Hyun; Yoon, Hye-On; Phan, Nhu-Thuc
Abstract : In an effort to reduce the experimental bias involved in the analysis of gaseous elemental mercury (Hg o ), the blank response from gold-coated adsorption tubes has been investigated using cold vapor atomic absorption spectrometry (CVAAS). Our study has been compared with our recent investigation on memory effect in a cold vapour atomic fluorescence spectrometry (CVAFS). The pattern of blank responses was quantified after loading different amounts of mercury and after different time intervals of 1, 14, and 45 days. In case of the one day interval, the result of five to six instant blank heating cycles confirmed successful liberation of mercury following the second and third blank heating cycles. The results of 14 or 45 days generally suggest that liberation of excess mercury is affected by both the initial loading amount and the length of storage time prior to analysis. We have demonstrated a possibly effective way to reduce memory effects. Some similarities of these results with those from CVAFS experiment suggests that the blank response is caused by a combination of mercury absorbed within the bulk gold and micro- and nanoparticles liberated during heating and not from coabsorbing interfering gaseous species.